Manajemen Logistik Obat Di Instalasi Farmasi Puskesmas Ciparay DTP Tahun 2022 - Ayu Laili; Syahidillah Anwar; Gunawan Irianto; Asep Dian Abdillah (LPPM Stikes Jenderal Achmad Yani Cimahi, 2022)
The role of the Puskesmas is important in providing treatment during the Covid-19 pandemic, so drug logistics management is needed. Regulation of the Minister of Health of the Republic of Indonesia Number 74 of 2016 concerning Standards for Pharmaceutical Services at Health Centers states that optimization in drug logistics management includes planning, procurement, storage, distribution, use and control of drugs that will be managed by the health service. The purpose of this study was to determine the Drug Management System in the Pharmacy Installation of the Ciparay DTP Health Center. This study uses a descriptive method with in-depth interviews and document review. The results showed that organizing and storing drugs were grouped alphabetically from AZ. This was done to facilitate the process of prescribing services and referring to the First In First Out system, specifically for Narcotic and Psychotropic Drugs, they are stored in a separate cupboard which is always locked and only if there are Narcotic or Psychotropic drugs that are prescribed by the Doctor then the cabinet is opened, recording the number of daily prescriptions, recording the type and amount of drug use per day, recording Certain Drugs (OOT) submitted to patients and recording requests and use of pharmaceutical preparations and BMHP by sub service units at the Puskesmas, in terms of inputting data on the Puskesmas Management Information System (SIMPUS) it has not gone well due to several factors, and the recording is still done manually and which must be copied or retyped later. Researchers suggest that the Puskesmas can improve the quality of human resources by means of training or socialization in terms of the Drug Management System, so that pharmaceutical services are better and faster.